2005
DOI: 10.1534/genetics.105.046540
|View full text |Cite
|
Sign up to set email alerts
|

A Screen for Nigericin-Resistant Yeast Mutants Revealed Genes Controlling Mitochondrial Volume and Mitochondrial Cation Homeostasis

Abstract: Little is known about the regulation of ion transport across the inner mitochondrial membrane in Saccharomyces cerevisiae. To approach this problem, we devised a screening procedure for facilitating the identification of proteins involved in mitochondrial ion homeostasis. Taking advantage of the growth inhibition of yeast cells by electroneutral K 1 /H 1 ionophore nigericin, we screened for genetic mutations that would render cells tolerant to this drug when grown on a nonfermentable carbon source and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Mdm31 was previously shown to be involved in mitochondrial morphogenesis, inheritance (Dimmer et al, 2005) and ion homeostasis (Kucejova et al, 2005). However, the precise molecular function of this protein is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mdm31 was previously shown to be involved in mitochondrial morphogenesis, inheritance (Dimmer et al, 2005) and ion homeostasis (Kucejova et al, 2005). However, the precise molecular function of this protein is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous deletion studies of MDM31 indicated that Mdm31p and Mdm32p control mitochondrial morphology (22,42) and are necessary for the proper inheritance and organization of mitochondrial DNA (22). The overexpression of MDM31 has not been described previously, so it is unclear whether the overexpression of MDM31 alone could cause the overabundance of mitochondria found in nrd1 mutants.…”
Section: Synthetic Lethal Interactionsmentioning
confidence: 99%
“…Analysis of such mutants could provide new insights into cellular ion homeostasis, as well as other related processes. In line with this assumption, we identified Δmdm31 and Δmdm32 among disruption mutants resistant to nigericin and their giant spherical mitochondria were shown to be swollen due to disturbed ion homeostasis (Kucejova et al 2005 (Kucejova et al 2005). Our screening of UV-induced nigericin and valinomycin resistant mutants yielded four independent clones, val R -1,2 and val/nig R -1,2, with disturbed mitochondrial morphology, one of them having also vacuolar defects (Petrezselyova et al 2007).…”
Section: Ionophore Resistance and Mitochondrial Morphologymentioning
confidence: 69%
“…The deletion of either one of the MDM31 and MDM32 genes is synthetically lethal with deletion of either one of the MMM1, MDM12, MDM10, and MDM34 genes (Dimmer et al 2005). In addition, in Δmdm31 and Δmdm32 mutants, mitochondria remain attached to actin filaments, but the colocalization of the MMM complex with mitochondrial DNA (mtDNA) is rare and the nucleoids are misshapen, aggregated and destabilized (Dimmer et al 2005;Kucejova et al 2005) similarly as in Δmmm1 (Hobbs et al 2001) and Δmdm34 (Youngman et al 2004). Therefore, Mdm31p and Mdm32p were proposed to play a role in nucleoid anchoring via cooperation with the MMM complex.…”
Section: Ambiguous Concept Of Mitochondrial Tubulationmentioning
confidence: 99%